2021
DOI: 10.5430/jha.v10n4p32
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine use in 2020 during the COVID-19 pandemic among community dwelling U.S. Medicare beneficiaries

Abstract: Objective: CMS reimbursement regulations for telemedicine changed after the onset of the COVID-19 pandemic. This study aimed to assess telemedicine utilization patterns offered by health care providers and used by Medicare beneficiaries during the COVID-19 pandemic during 2020.Methods: This study used the Fall 2020 Medicare Current Beneficiary Survey (MCBS) supplemental COVID-19 survey to identify Medicare beneficiaries (≥ 65 years) with a regular place for medical care that offered telemedicine during 2020. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Internet access was defined according to whether the respondent had access to the internet. Having previously used video or voice calls was defined according to whether the respondent had previously used video or voice calls (for any reason) ( 19 , 20 ). Telehealth-related technology access was defined according to whether the respondent owned a computer, smartphone, or tablet.…”
Section: Methodsmentioning
confidence: 99%
“…Internet access was defined according to whether the respondent had access to the internet. Having previously used video or voice calls was defined according to whether the respondent had previously used video or voice calls (for any reason) ( 19 , 20 ). Telehealth-related technology access was defined according to whether the respondent owned a computer, smartphone, or tablet.…”
Section: Methodsmentioning
confidence: 99%
“…20,21 Specifically, studies examining telehealth adoption during the pandemic among Medicare recipients found that patients who identified as non-Hispanic Black and those with comorbidities were more likely to use telehealth services when offered by their usual providers. [21][22][23][24] Similarly, another study also found individuals from racially minoritized groups were less likely to have telehealth visits compared to their White counterparts. 25 Other studies 26,27 examined disparities in specific telehealth utilization by highlighting that patients who were older, Black, and were Medicaid recipients were less likely to have video telehealth visits compared with audio-only telehealth visits during the COVID-19 pandemic.…”
mentioning
confidence: 93%
“…Previous literature found disparities among older adults in telehealth accessibility and uptake related to sociodemographic factors, including gender, race, and income during the COVID-19 pandemic 20,21. Specifically, studies examining telehealth adoption during the pandemic among Medicare recipients found that patients who identified as non-Hispanic Black and those with comorbidities were more likely to use telehealth services when offered by their usual providers 21–24. Similarly, another study also found individuals from racially minoritized groups were less likely to have telehealth visits compared to their White counterparts 25.…”
mentioning
confidence: 97%